Pengaruh substitusi tepung buah pepaya pada produk crackers dari tepung mocaf dan susu sapi segar - Salsabella, Amanda Khairani; Purwani, Eni; Sofyan, Aan (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Crackers are snack foods with potential as functional foods using local ingredients. Modified Cassava Flour (MOCAF) is a gluten-free carbohydrate source but low in protein and minerals. Fresh cow’s milk provides calcium and protein, while pepaya flour substitution is expected to enhance mineral, protein, and reducing sugar content. This study aimed to analyze the effect of pepaya flour substitution on calcium, magnesium, protein, and reducing sugar content in crackers made from MOCAF and fresh cow’s milk. This experimental study used a completely randomized design with pepaya flour substitution levels of 0%, 20%, 30%, and 40%. Calcium and magnesium were analyzed using ICP-OES, protein using the Kjeldahl method, and reducing sugars using the Luff–Schoorl method. Data were analyzed using one-way ANOVA followed by Duncan’s multiple range test to determine differences among treatments. pepaya flour substitution significantly affected calcium, protein, and reducing sugar content (p<0.05), with the highest increase at 40% substitution. Magnesium also increased, but no significant difference was observed between 30% and 40%. Fresh cow’s milk contributed to higher calcium and protein, while pepaya flour enhanced magnesium and reducing sugar content. Substituting pepaya flour in MOCAF crackers with fresh cow’s milk increases calcium, magnesium, protein, and reducing sugar content, with greater effects at higher substitution levels.